A Re-Examination of Responding on Ratio and Regulated-Probability Interval Schedules - Perez-Riveros, O (Academic Press, 2018)
The higher response rates observed on ratio than on matched interval reward schedules has been attributed to the differential reinforcement of longer inter-response times (IRTs) on the interval contingency. Some data, however, seem to contradict this hypothesis, showing that the difference is still observed when the role of IRT reinforcement is neutralized by using a regulated-probability interval schedule (RPI). Given the mixed evidence for these predictions, we re-examined this hypothesis by training three groups of rats to lever press under ratio, interval and RPI schedules across two phases while matching reward rates within triads. At the end of the first phase, the master ratio and RPI groups responded at similar rates. In the second phase, an interval group yoked to the same master ratio group of the first phase responded at a lower rate than the RPI group. Post-hoc analysis showed comparable reward rates for master and yoked schedules. The experienced response-outcome rate correlations were likewise similar and approached zero as training progressed. We discuss these results in terms of a contemporary dual-system model of instrumental conditioning. © 2018 The Authors